Effects of native and pregelatinized starches on feed physical properties, digestibility, growth, nutrient utilization and histology of liver and intestine of juvenile tinfoil barb (Barbonymus schwanenfeldii, Bleeker 1853 ) - Mohamed Nafees, Mohamed Salihu; Kamarudin, Mohd Salleh; Karim, Murni; Hassan, Mohd Zafri; de Cruz, Clement Roy (Hindawi, 2022)
A 56-day feeding trial was conducted to evaluate the effects of native and pregelatinized starches on feed quality, digestibility, growth, nutrient utilization, intestinal α-amylase activity, plasma biochemical parameters and liver and intestine histology of Barbonymus schwanenfeldii juveniles. Six isonitrogenous and isocaloric diets were prepared using native and pregelatinized corn, sago and tapioca starches. Each diet was randomly assigned to triplicate groups of 20 fish (3.32 ± 0.02 g). Results revealed an interactive influence of starch source and pregelatinization (p < 0.05) on pellet expansion, sinking velocity, durability, water absorption index and water stability. However, the diets did not affect feed intake, growth and feed efficiency of fish. Accordingly, whole-body composition, nutrient retention and body indices were also insignificant. Digestibility of dry matter, protein and carbohydrate depended on both starch sources and forms (p < 0.05) while α-amylase activity varied with starch sources and gut regions (p < 0.05). Intestinal villus height of fish varied (p < 0.05) with starch sources and forms, whereas villus width and area differed among combinations of starch sources and forms (p < 0.05). Likewise, hepatocyte size of fish was different among dietary starch source and form combinations. However, the diets did not alter the plasma biochemical composition of fish. Overall, it was concluded that though pregelatinized starch improved pellet quality and nutrient digestibility, tinfoil barb juveniles could equally utilize 19.25% native and pregelatinized corn, tapioca and sago starches.